PERPATAHAN FATIK MATERIAL ALUMINIUM 2024-T3 DENGAN PENGELASAN FSW - Pujono Pujono (Infotekmesin, 2018)
Resilient, machine processed, shapped aluminium using pulling power for pure aluminium with 4-5kgf/mm2. Aluminium fusion with series 2024-T3 is a metal fusion whose low weldability so it is very difficult to be conducted the welding process because it tends to occur hot cracking or being porous, and precipitation hardening when conducting welding process due to segregation of copper (Cu) fusion subtance. One of welding method to obtain the good aluminium welding result is by using FSW (friction stir welding). The purpose of this research is to find out the shape and type of fracture on aluminium fusion with FSW welding by dealing TTT. The fracture is created from fatik substance test. The reserach method was conducted by welding of plate aluminium fusion 2024-T3 using FSW technique by dealing transient thermal tensioning (TTT). Transient thermal was conducted by resigning heater line with weld tool/pin. The speed of determined FSW welding was 11 mm/minutes and 1200 rpm. The conducted test was fatigue test and factografi test with SEM. The result of the reserach shows that the number of fatik test cycle is 765.250 with sigmoidal curve visually. Then, the result of fractography using SEM shows that the occured fracture is brittle.